PLASMA PROGESTERONE PROFILE DURING GESTATION AND PERIPARTUM PERIOD IN CORRIEDALE SHEEP - GANAIE, B A; KHAN, M Z; QURESHl, S; ISLAM, R; WANI, G M (The Indian Journal of Animal Reproduction, 2023)
Fifty Corriedale ewes aged between 3.5-4.5 years, weighing 35-40 kg and maintained at SheepResearch Station, Srinagar under semi-intensive type of housing system were used. The ewes weretupped after proper estrus detection and the blood samples were taken fortnightly starting from day oftupping till 15 days post-tupping. The average gestational length was 149 ± 2 days. Plasma progesteronewas estimated by Enzyme Immune Assay (EIA) using ELISA kit. On the day of tupping the meanplasma progesterone concentration was 0.65 ± 0.13 ng/ml and increased significantly (P
Keywords: Plasma Progesterone Profile; Gestation; Pregnancy diagnosis; Corriedale sheep